The Influence Of Librarians' Competence On Their Performance At The Jatinangor Institute Of Home Affairs Governance (IHAG) Library (Institut Pemerintahan Dalam Negeri, 2022)
The purpose of this study is to determine the influence of librarians' digital competence on their performance at the Jatinangor IHAG Library. This is a quantitative study with data collected from 30 respondents through questionnaires. The statement items from Marguna and Sangiasseri (2020) were used to provide answers to the problem formulation. The results showed that the librarians' digital competence and performance are included in the fairly good category. In conclusion, Digital Competence (X) as the independent variable influences the dependent one, namely Librarians' Performance (Y), with a value of 31.1%.